Defining critical parameters in a luminescent downshifting layer for PV enhancement - Mc Cormack, Sarah; Cass, Bill; Chandra, Subhash; Ayala Barragan, Maria F. (My University, 2021)
This paper presents the study and evaluation of luminescent down shifting (LDS) layers doped with organic dyes and their compatibility with different types of solar cells. In this study commercial dyes in the Lumogen-F series (BASF) Violet 570, Orange 240, Red 300, Yellow 083, and Yellow 170 were considered for this analysis. It was found that while organic dyes fulfil important characteristics for luminescent materials for LDS such as high photoluminescent quantum yield, small radiative overlap, absorption in or close to the UV range and emission in the visible spectrum. Nevertheless, due to their low Stokes Shift, organic dyes do not entirely align to the spectral response of solar cells as the spectral matching of the emission and absorption are characteristics that depend on the external quantum efficiency of the solar cell. In this paper a design matrix was developed for the commercial dyes outlined and different solar cell types. For different parameters of the luminescent materials and solar cells the optimized LDS layer can be chosen.
World Renewable Energy Congress
PUBLISHED
Keywords: Downshifting; Luminescence; Downshifting Layers; Photovoltaics